PENGARUH BEBAN KERJA, SELF EFFICACY DAN MORAL REASONING AUDITOR TERHADAP KUALITAS AUDIT - Sutarminingsih, Sutarminingsih; Hifni, Syaiful; Hikmah, Nor (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2023)
This study aims to examine and analyze the effect of workload, self-efficacy and moral reasoning auditors on audit quality at the Provincial/District/City Inspectorate of South Kalimantan. The population in this study were all auditors working at the Inspectorate in South Kalimantan with a population of 183 (one hundred and eighty three) auditors. Sampling was done by using the purpose sampling method, amounting to 135 respondents. The primary data collection method used is the questionnaire method. The data were analyzed using multiple linear analysis techniques. The conclusion in this study uses Moderate Regression Analysis (MRA) with the help of the SPSS version 23 program. The results show that there is no significant effect of the auditor's workload variable on Audit Quality, there is a significant effect of the Auditor Self Efficacy variable on Audit Quality, not There is a significant effect of the Moral Reasoning Auditor variable on Audit Quality.